2019
DOI: 10.1214/18-aoas1217
|View full text |Cite
|
Sign up to set email alerts
|

Modelling ocean temperatures from bio-probes under preferential sampling

Abstract: In the last 25 years there has been an important increase in the amount of data collected from animal-mounted sensors (bio-probes), which are often used to study the animals' behaviour or environment. We focus here on an example of the latter, where the interest is in sea surface temperature (SST), and measurements are taken from sensors mounted on Elephant Seals in the Southern Indian ocean. We show that standard geostatistical models may not be reliable for this type of data, due to the possibility that the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
(90 reference statements)
0
3
0
Order By: Relevance
“…The biasing effects of PS on spatial prediction has been clearly demonstrated across a wide range of fields and can be severe in magnitude [Diggle et al, 2010, Watson et al, 2019b, Pennino et al, 2019, Dinsdale et al, 2019. Thus, PS should not be ignored in spatial analyses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The biasing effects of PS on spatial prediction has been clearly demonstrated across a wide range of fields and can be severe in magnitude [Diggle et al, 2010, Watson et al, 2019b, Pennino et al, 2019, Dinsdale et al, 2019. Thus, PS should not be ignored in spatial analyses.…”
Section: Discussionmentioning
confidence: 99%
“…PS should also be considered in the analysis of environmental data recorded from tagged animals. Dinsdale et al [2019] demonstrated this with a case study using sea surface temperature recordings from tags attached to Elephant Seals in the Southern Indian ocean. The seals' preference for cooler waters led to biased 'naive' spatial estimates of sea surface temperature.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation